The Black Sea Physical, Environmental and Historical Perspectives - Vespremeanu, Emil (Springer Geography,, 2018)
This book underpins the geography of the Black Sea, covering topics such as morphology, morphography, geology, and history of the Black Sea. It also discusses environmental aspects affecting the population in the Black Sea's coastal settlements and looks to the future of the Black Sea region. This book covers a gap in research in the field of world regional geography of the Black Sea by providing a comprehensive methodology and terminology to readers, students and teachers in the field.